Concreto com rejeito de sinter feed: estudo comparativo de desempenho e caracterização microestrutural - Ayrton Vianna Costa (2016)
Context: The iron ore tailings generated at mining companies has created enormous problems. Their use as aggregate material for the production of concrete and mortars, in total or partial replacement to sands conventionally used, is a little studied matter, but can settle costs to mining companies in their inventory, control and disposal, besidesbenefiting the environment significantly. Objectives: Develop comparative studies in mortar and concrete produced with the iron ore tailings generated in the sinter feed production process in relation to their corresponding ones produced with conventional aggregates. Evaluate the corresponding microstructures and carry out physical tests tovalidate the use of these tailings in natural sands partial or total replacement in mortar and concrete. Materials: Sinter feed tailings produced by processing in a jigging facility, Portland CP II-E 32 and CP IV-RS 40, IPT normal sand, medium size common washed quartz sand, limestone grit 0 and 1, multifunctional plasticizer additive and tap water.Methods: The final iron ore tailings were characterized by grain size analysis, specific surface area and porosimetry by nitrogen adsorption/condensation and mineralogical and microstructure analysis. Molded specimens of mortar and concrete were made with and without the tailings. Microstructure analyses by scanning electron microscopy and energy-dispersive microanalysis were done on both samples. The following comparative physical tests have been carried out, as well: resistance to compression, traction by diametral compression, dynamic modulus, dry abrasion and under water and capillarity absorption in the concretes samples. Results: It was detailed for each physical test held, in each concrete mix with the tailings and in their respective ages,the percentage above or below the performance observed in relation to the concrete reference mix (without tailings use). The performances values were also qualitatively highlighted, considered superior or inferior as positive or negative the value of the comparative percentage. Conclusion: The use of sinter feed tailings as a secondary member of the blends of aggregates in concrete production is considered feasible,under specific circumstances and purposes, not only in terms of their observed characteristics and performances, but mainly due to the ecological and sustainability conveniences offered by its use. The employment of the sinter feed tailings in the production of conventional concrete (fck until 30MPa) is proven. The use of sinter feed tailings as an aggregate in plastic consistency concrete, with respect to improving itsperformance in hydric abrasion needs further review, including specific characterization and the choice of the specific sinter feed tailings (presence different varieties of the mineral goethite). The microstructure of the paste/aggregate interface of the mortar and the concretes produced with the sinter feed tailings presents the euhedral hydrated cement phases little developed, showing some shrinking as compared to its classic morphology.